(untitled) (Journal of Global Accounting, 2024)
The study investigated the effect of tax aggressiveness on liquidity management of listed manufacturing firms in Nigeria. The study uncovers the surprising link between tax aggressiveness and liquidity management that will reshape financial strategies for manufacturing firms. Based on the objectives of the study, three research questions and hypotheses were formulated. The study covers a ten-year period from 2014 to 2023 because this period holds the most recent annual financial statement and tax filings of listed manufacturing firms are publicly available providing sufficient data to analyze trends and effects over time. The specific objective was to determine the effect of book-tax difference on liquidity ratio (current ratio of listed manufacturing firms in Nigeria. The study employed Ex-post facto research design in which secondary data were collected from annual reports and financial statements of five purposively selected manufacturing companies from 2014 to 2023. Panel least square regression was adopted for the analysis using E-views 10 statistical tools. Findings indicate book-tax differences has significant negative effect on current ratio while cash effective tax rate and effective tax rate have positive significant effect on current ratio. Tax aggressiveness undermines liquidity position when aggressively pursued beyond ethical and compliance boundaries. However, legitimate tax planning enhances cashflows and liquidity. The study concluded that tax aggressiveness and liquidity management decisions require prudence, transparency and consideration of stakeholders’ interests to ensure sustainable competitiveness and growth. The study recommended among others that listed manufacturing firms should re-evaluate their tax planning strategies and consider prioritizing financial stability and liquidity management over aggressive tax minimization tactics that rely on high book-tax differences. Maintaining stronger liquidity positions will make the firms less vulnerable to short-term financial stresses.